The Role of Fishermen in Preserving the Environment of Sukalila Estuary, Cirebon City - Nasehuhdin, Nasehuhdin; Ramadhani, Tri Oktavia; Nafisah, Uswah (Transpublika Publisher, 2025)
This study aims to examine the role of fishermen in preserving the environment in Muara Sukalila, Cirebon City. As a coastal community group that relies directly on marine resources, fishermen have a vital interest in maintaining the sustainability of aquatic ecosystems. This research employed a qualitative approach with data collection techniques including interviews, observations, and documentation. The findings reveal that fishermen in Muara Sukalila are actively involved in various environmental conservation practices, such as avoiding the use of destructive fishing gear, cleaning up waste around the estuary, and maintaining catch limits to prevent overfishing. Additionally, local wisdom plays a significant role in fostering ecological awareness in the fishermen’s daily lives, including prohibitions against dumping waste into the sea and communal efforts to maintain environmental cleanliness. However, challenges such as limited government support, industrial waste pollution, and climate change continue to pose serious obstacles. Therefore, collaboration among fishermen, the government, and the wider community is essential to strengthen sustainable efforts in coastal environmental preservation.